Atividade inseticida de extratos e óleos essenciais de espécies do Gênero Lippia contra Callosobruchus maculatus (Fabricius, 1775) e Nasutitermes corniger (Motschulsky, 1855) - Santos, Daiane Rodrigues dos (2017)
The exploitation potential of new biopesticides sources is very broad in Brazil and worldwide. In the past few years, the search for these products has been intensified due to serious health and environmental issues caused by the use of synthetic insecticides. In this context, essential oils and extracts of vegetal species have been considered as an alternative to agriculture. Thus, the aim of this work was to test the insecticidal potential of species belonging to the genus Lippia Lippia insignis Mondenk 1976, Lippia lasiocalycina Schauer, 1832 e Lippia thymoides Martius & Schauer, 1832 no controle de insetos-praga que provocam danos econômicos (Callosobruchus maculatus Fabricius, 1775 e Nasutitermes corniger Motschulsky, 1855) in the control of insect-pest responsible for economic damage (Callosobruchus. maculatus and Nasutitermes corniger). The samples were collected in the experimental area in the Horto Florestal (UEFS) and after the material was dried, the essential oils were extracted and the extracts were prepared. In vitro trials were performed in order to verify the effects of essential oils and extracts against C. maculatus and N. corniger. The methodology of exposition to contaminated surface, testing an initial concentration of aqueous and methanolic extract and essential oils was adopted to determine the insecticidal activity of extracts and oils. The mortality was verified 24 and 48 hours after treatment application, and the product with major potential on the insect mortality was diluted in different concentrations to determine the medium lethal concentration (LC50). The repellent activity against C. maculatus and N. corniger was evaluated. Moreover, specific tests with C. maculatus investigated the product efficiency in two methods of application, as well as the quantification and identification of chemical constituents present in the studied species oils using GC/FID and GC/MS techniques. The results obtained revealed, occurrence highlighted of β-mirceno and E -ocimenona in the sample of L. lasiocalycina, in L. insignis were prominent β-mirceno e o limoneno. For L. thymoides the main constituents were: E-cariofileno e o óxido de cariofileno.for C. maculatus, the essential oil of L. insignis stood out as insecticidal activity with CL50 of 3,11 µl/ml. Although both methods of application showed efficiency in the control of this insect-pest, there was no repellent activity verified in the oil of L. insignis (5µl/ml). For N. corniger, the essential oils of all tested species, as well as the methanolic extract of L. insignis exhibited promising results in the control of this insect-pest. It was also verified that L. lasiocalycina possessed lower LC50 (0,47 µl/ml) compared to L. insignis (0,88 µl/ml) and L. thymoides (3,64 µl/ml), while the LC50 of L. insignis methanolic extract was 27,84 mg/ml. Furthermore, essential oils and methanolic extracts of Lippia studied species revealed repellent activity in the N. corniger in vitro trials.